Recent Understanding of Colorectal Cancer Treatment - Jeong, Keun-Yeong (IntechOpen, 2022)
From surgery to chemotherapy and radiotherapy, attempts to conquer colorectal cancer have been ongoing for a century. Due to these efforts, the mortality rate of colorectal cancer has decreased by about 3% per year for the past 10 years. Progress in reducing mortality from colorectal cancer can be accelerated by improving screening and the use of standard care in all populations. In recent years, advanced knowledge and technologies for better efficiency in targeting colorectal cancer have been developed to improve conventional therapeutics or to propose new therapies as standard regimens. This book discusses diagnostics as well as surgical techniques using robotics, immunotherapy, and radiology-based therapy for colorectal cancer. The section on diagnostics provides information on proteomics, organoid culture techniques, and various candidate markers. The section on treatment discusses robotic surgical techniques for rectal cancer care and multidisciplinary approaches for colorectal cancer treatment. The book also examines the latest in supportive care from a nutritional and metabolic point of view.